S-100B in the follow-up of patients with stage III and IV melanoma: pursuit of the Holy Grail - Ackermans, L. L. G. C.; Aldenhoven, L.; Bosmans, J. W. A. M.; Van Kuijk, S. M. J.; Van Bastelaar, J. (International Surgery Journal, 2022)
Background: Patients with stage III-IV melanoma are at considerable risk for disease recurrence. Early detection of recurrence is important to optimize immunotherapy administration and improving progression-free and overall survival. S-100B can be used as tumor marker to evaluate whether patients are at risk for developing disease recurrence or progression. It could be a promising tool to determine whether patients need to receive additional diagnostic procedures. However, implementation in routine clinical setting is limited. Hence, this study aimed to evaluate the value of S-100B as a decision tool for the need to perform an 18F-fluorodeoxyglucose (FDG) positron emission tomography with computed tomography (PET/CT) to confirm disease recurrence or progression in stage III-IV melanoma patients. Methods: Data of 51 stage III-IV melanoma patients, presenting for follow-up after surgery with curative intent, was retrospectively extracted from a single-center electronic patient record system. 18FDG-PET/CT was performed based on clinical signs or elevated S-100B levels. S-100B measurements were treated as independent data points. Results: Fifteen out of 303 S-100B levels were elevated. Six elevated levels were causes by disease progression; 4/6 measurements were noted with concurrent clinical signs. Twenty-four events of disease progression were confirmed. The sensitivity and specificity of S-100B serum test were 25.0% [95% CI (9.8-46.7)] and 96.8% [95% CI (94.0-98.5)]. The positive predictive value (PPV) and negative predictive value (NPV) of S-100B were 40.0% [95% CI (20.6-63.2)] and 93.8% [95% CI (92.2-95.0)]. Conclusions: Elevated S-100B levels did not exclude nor indicate metastatic or recurrent disease in this study. Using S-100B in routine clinical setting does not seem to be of additional value.